Transformative learning theory in lifelong learning research: A systematic review of its functions, extensions, and holistic dimensions - Cho, Yongsic; Charungkaittikul, Suwithida; Soopunyo, Weerachat (Edelweiss Applied Science and Technology, 2026)
As societies face rapid technological and social change, lifelong learning has become essential for individuals to continuously adapt and reconstruct their knowledge and identities. In this context, Transformative Learning Theory (TLT) provides a critical lens for understanding how learners engage in reflection and achieve perspective transformation. Despite their conceptual alignment, the application of TLT in lifelong learning research remains fragmented, particularly with respect to its holistic dimensions. This study systematically examines how TLT is employed in the literature, focusing on its functional roles, theoretical positioning, and core components. Guided by the PRISMA framework, a systematic review of 52 peer-reviewed articles published between 2015 and 2024 was conducted. Qualitative content analysis was applied to classify studies across three analytical dimensions: functional use of TLT, theoretical positioning of holistic approaches, and components of transformation. The findings indicate that TLT is most frequently used as a core theoretical framework (73.1%), while holistic components are widely identified as explicit (82.7%), implicit (80.8%), and emancipatory (75.0%), but are not consistently integrated within individual studies. This study contributes to theory development by advancing a more integrative conceptualization of holistic transformative learning and offers implications for the design of lifelong learning environments that support multidimensional and sustained transformation.